Nonlinear analysis of reinforced and composite columns in fire (Fracture and Structural Integrity, 2016)
The paper describes a customer project, the objective of which was to develop a software program for the calculation of reinforced concrete and steel/concrete composite columns subjected to various loadings and exposed to normal temperature or to fire conditions. Such analysis required the use of two Finite Element calculation cores (i) for thermal analysis and (ii) for geometrical and material non-linearity. Calculation cores were connected to graphical user interface via open interface – IDEA Open Model.
Keywords: Column; Concrete; Composite; Analysis; Non-linear; Fire